Enhancing collaborative competence and learning motivation through group investigation in civic education - Muhammad Syamsuddin Syams; Mukhamad Murdiono (Privietlab, 2025)
Many Civic Education courses in higher education suffer from low student engagement, primarily due to passive learning models that limit motivation and collaborative interaction. Although cooperative learning strategies have been widely studied in primary and secondary education, their integration into civic-oriented university courses remains underexplored. This study investigates the application of the Group Investigation (GI) model to improve university students’ learning motivation and collaboration in Civic Education. Employing a participatory action research approach in a higher education setting, the study was conducted in two cycles involving 68 undergraduate students enrolled in a general education course. Data were collected using observation sheets, questionnaires, interviews, and documentation. Quantitative data were analyzed using descriptive statistics and paired-sample t-tests, while qualitative data were examined through thematic analysis. The results showed a statistically significant improvement in students' learning motivation (from M = 73.7 to M = 84.2, p < 0.001) and collaborative character (from M = 71.4 to M = 83.6, p < 0.001). These findings suggest that the GI model supports both the affective and cognitive aspects of learning by promoting student autonomy, inquiry-based dialogue, and mutual responsibility. Theoretically, this study contributes to the literature on cooperative learning in higher education and the design of democratic learning environments in Civic Education. Practically, it offers an adaptable model for educators seeking to develop soft skills through group-based inquiries. The research implies that integrating cooperative methods into civic education may offer a viable pathway for developing character and motivation in future professionals.